2020
DOI: 10.2147/copd.s249534
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sarcopenia Is an Independent Risk Factor for NAFLD in COPD: A Nationwide Survey (KNHANES 2008–2011)</p>

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is highly prevalent in patients with chronic obstructive pulmonary disease (COPD) and is independently associated with cardiometabolic comorbidities and systemic inflammation. Although several factors are associated with NAFLD, the influence of sarcopenia on NAFLD has not been fully determined in patients with COPD. We explored whether sarcopenia is associated with NAFLD in a COPD population. Methods: Data from the Korean National Health and Nutrition Examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Third, we were unable to adjust for inflammation and insulin resistance due to the unavailability of these factors in the current NHANES dataset. Although we tried to adjust known risk factors between two conditions, we also could not eliminate the possibility of unadjusted residual confounders in this study, such as the presence of chronic obstructive pulmonary disease that may affect the risk of two conditions [42]. Fourth, there are known tendencies of difference between liver stiffness or CAP measurement and probe types of transient elastography, and it is possible that the NAFLD and significant fibrosis may have been misclassified.…”
Section: Discussionmentioning
confidence: 98%
“…Third, we were unable to adjust for inflammation and insulin resistance due to the unavailability of these factors in the current NHANES dataset. Although we tried to adjust known risk factors between two conditions, we also could not eliminate the possibility of unadjusted residual confounders in this study, such as the presence of chronic obstructive pulmonary disease that may affect the risk of two conditions [42]. Fourth, there are known tendencies of difference between liver stiffness or CAP measurement and probe types of transient elastography, and it is possible that the NAFLD and significant fibrosis may have been misclassified.…”
Section: Discussionmentioning
confidence: 98%
“…Sarcopenia is an independent risk factor for NAFLD in COPD. It is interesting that sarcopenia in patients with COPD is associated with an increased risk of NAFLD and more severe fibrosis independent of lung function and metabolic characteristics [ 228 ]. Moreover, worsening histologic severity of NAFLD, especially at the fibrosis stage, is accompanied by decreased lung function [ 229 ].…”
Section: Lipid Metabolism Disorders In the Development And Progression Of Copdmentioning
confidence: 99%
“…Several lung diseases such as TB, chronic obstructive pulmonary disease (COPD), and asthma can result in systemic inflammation, which can cause muscle loss and further exacerbate skeletal muscle detriment. 21 In addition, several studies showed that TB is also a risk factor for COPD and can increase the risk for restriction dysfunction due to residual lung damage. [37][38][39][40][41][42] These factors may contribute to sarcopenia in TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Definition of sarcopenia Sarcopenia was defined using the ASM in one of three ways: "sarcopenia_BMI = ASM/BMI," "sarcopenia_height = ASM/height 2 ," and "sarco-penia_weight = ASM/weight * 100," as mentioned in a previous study. 21 Sarcopenia was measured using the ASM/BMI, as recommended by the Foundation for the National Institutes of Health (FNIH) for men (<0.789) and women (<0.512); 22 using ASM/height 2 , as recommended by the Asian Working Group for Sarcopenia (AWGS) for men (<7.0) and women (<5.4); 23 and using ASM/weight × 100, which was calculated to be less than two standard deviations by the sex-specific mean for healthy young adults according to the 2008-2011 KNHANES data for men (<29.0) and women (<22.9). [24][25][26] Dietary assessments For dietary surveillance, well-trained dietitians conducted in-person interviews with participants, using 24-h recall methods and food frequency questionnaires (FFQs).…”
Section: Demographic and Anthropometric Assessmentsmentioning
confidence: 99%